Factors that influence the transition from high school to higher education : the case of the Junior Tukkie Programme - Sehoole, Molatlhegi Trevor Chika (University of Pretoria, 2018)
The study investigated the factors that influence new students’ transition from high school to higher education. The research activities involved a case study of members of the JuniorTukkie Empowerment initiative (between 2009 and 2013). The study’s main objective was to identify the factors (academic and non-academic) and attributes (such as family background, socio-ecnomics status, prior higher education experience skills, abilities, etc.) that enabled new students to transit successfully and complete their first-year courses in one academic year. Accurate identification of such factors will in future benefit the JuniorTukkie initiative, whose programmes are designed to facilitate successful transitions from high school to tertiary education for prospective students. The study’s theoretical framework prescribed the collection of quantitative (online questionnaire) and qualitative (focus-group interviews) data. The quantitative research phase involved 256 respondents, of which 47 members participated in the following qualitative research phase. A case study research design, focusing on the possible influential factors and students’ attributes during the transitional stage, allowed the researcher to gain a comprehensive understanding of nearly all aspects of the JuniorTukkie initiative’s programmes. Almost all research participants had successfully completed their first-year studies in one year, securing the validity of obtained data. The findings revealed which factors significantly contributed to successful transitions and completion of first-year courses, and which factors were less influential. This research revealed that the specific challenges associated with new students’ transitional experiences from high school to higher education necessitate the strategic intervention of initiatives (such as JuniorTukkies), whose responsibility it will be to implement a variety of programmes to address all academic and non-academic transitional factors.